Teacher pay and student performance: evidence from the Gambian hardship allowance. Issue 2 (3rd April 2018) - Pugatch, Todd; Schroeder, Elizabeth
ABSTRACT: More than two dozen developing countries have implemented policies to increase teacher compensation in rural schools. We evaluate the impact of the Gambian hardship allowance, which provides a salary premium of 30–40% to primary school teachers in remote locations, on student performance. A geographic discontinuity in the policy's implementation provides identifying variation. We find no effects of the hardship allowance on average test scores. However, we find suggestive evidence that student performance improved at the top of the test score distribution and fell at the bottom. Our findings indicate that the substantial, unconditional salary increases earned by Gambian teachers had little to no effect on average student performance, with gains limited to the best students.